On existence of a paramagnetic contribution to the susceptibility of a mesoscopic cylindrical normal metal-superconductor structure - Gogadze, G.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The density of states N(e) of a mesoscopic cylindrical structure consisting of a normal pure metal and a superconductor has been calculated using the Gorkov–Green functions. It is shown that magnetic fluxes ofcertain values cause resonance spikes of N(e) suggesting a large-amplitude paramagnetic contribution which accounts for the reentrant effect detected (P. Visani, A.C. Mota, and A. Pollini, Phys. Rev. Lett. 65, 1514 (1990)).